A Systematic Literature Review of Bilingual Education Models: :Approaches and Educational Outcomes - Gersalia, Angela; Estremera, Michael (International Journal of Language Teaching and Education, 2025)
This systematic literature review explores various bilingual education models—Dual Language Immersion (DLI), Two-Way Immersion (TWI), Transitional Bilingual Education (TBE), and Maintenance Bilingual Education (MBE)—to assess their pedagogical approaches and corresponding educational outcomes. 1,128 articles were identified from databases including ERIC, JSTOR, Google Scholar, Wiley Online Library, and SAGE Journals and screened using the PRISMA framework. Twenty-one studies met the inclusion criteria. The findings show that the DLI model consistently produces strong literacy, academic performance, and language retention results. The TWI, TBE, and MBE models yielded more varied outcomes. Geographic analysis revealed a research concentration in North America, Europe, and Asia. This review highlights practical approaches for educators and policymakers while identifying gaps for future research.